Canarium schweinfurthii stone-derived biochar: A promising adsorbent for crystal violet dye removal - Marcellinus O. Ani; Matthew C. Menkiti; Chukwunonso O. Aniagor; Cyril E. Nworie; Daniel O. Ochi (Results in Surfaces and Interfaces, 2023)
In this study, the effectiveness of C. schweinfurthii biochar (CSSB) for the adsorption of aqueous crystal violet dye (CVD) was investigated. Batch mode experiments were conducted to examine the influence of different process variables on the dye adsorption capacity of the CSSB. The surface chemistry and morphology of the adsorbent were elucidated using the Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy/energy dispersion X-ray (SEM/EDX), respectively. At optimum adsorption conditions (50 mg/L adsorbate concentration, 303 K and 35 min), a maximum removal efficiency of 90.04% was achieved. The experimental equilibrium and kinetic data were best fit to the Freundlich isotherm and Elovich kinetics models, respectively. The thermodynamic evaluation showed average Gibbs free energy (ΔGo), entropy change (ΔSo) and enthalpy change, (ΔHo) values of −1647.18 KJ/mol, −58.69 KJ/mol K and −173.10 KJ/mol, respectively. These thermodynamic data demonstrated that CVD adsorption onto CSSB was favourable, spontaneous, and exothermic. Any doubts about the adsorbent's economic viability were allayed by its projected cost of 0.0003 USSD/g per gram of adsorbate. Thus, according to the experimental results, the CSSB is considered an economical, effective, and environmentally friendly adsorbent for aqueous CVD adsorption.